Case report: A rare appearance of preretinal deposits in a patient with uveitis: multimodal imaging observation - Cheng, Yizhe; Chen, Chunli; Xiao, Yuanyuan; Wang, Shuang; Wang, Sihui; Peng, Xiaoyan (Frontiers in Medicine, 2023)
Background Uveitis is a disease presenting with varied clinical symptoms and potentially devastates visual function. Here, we report a patient with uveitis exhibiting a rare appearance of preretinal deposits (PDs). Case presentation A 49-year-old female showed vitreous opacity and perivascular white PDs involving veins and arteries. The interferon-gamma release assay was strongly positive and chest computed tomography showed signs of calcified nodules; other tests were unremarkable. The patient was diagnosed with uveitis and tubercular infection. The patient was given systemic anti-tubercular therapy and steroids, which were subsequently combined with immunosuppressants. The shrinkage of HRD was more sensitively observed with OCT than on photographs during follow-up visits. The right eye was relieved subsequently, but the left eye showed vitreous opacity and responded poorly to the treatment. Three months after the dexamethasone intravitreal implant, the perivascular deposits in the left eye disappeared and the vitreous opacity was relieved. Conclusion PDs can appear as spotted deposits in the posterior pole and segmental deposits in the periphery in patients with uveitis, which mainly involves the vitreous cavity and is easily confused with retinal vasculitis. OCT can more sensitively observe the response than other examinations.